Pengembangan Sistem Informasi Pengelolaan Dokumen Penjaminan Mutu Internal berbasis Website di SMKN 2 Magelang - Gita Sintya Pratiwi; Priyanto (Journal of Information Technology and Education (JITED), 2024)
The aims of this research are: (1) to develop a web application for the recapitulation of internal quality assurance documents at Magelang 2nd State Vocational High School; (2) to know the quality of the web application for the recapitulation of internal quality assurance documents at Magelang 2nd State Vocational High School developed based on functional suitability testing aspects, to test the functionality of web applications and usability, to test the ease of users in using this web application. The method of this research is Research and Development. The application development method used is the waterfall model, which goes through 5 stages: communication, planning, modelling, construction, and deployment. The research subjects for functional suitability testing were 2 expert respondents in the field of website development and the subject for usability testing consisted of 15 respondents from TPMS and schoolwork units. Data collection was carried out by observation, interviews, and questionnaires. The result of this research is the Simuin web application, to recapitulate internal quality assurance documents at Magelang 2nd State Vocational High School developed using the Laravel framework. The results of testing the Simuin web application show that this application has met the ISO / IEC 25010 standard. In testing the functional suitability aspect, it gets a score of 100% which means all functions can run well and are "very feasible" to use. The usability aspect, it gets an average score of 72.667 so it got a grade of B which means that the web application is easy to use.